2021
DOI: 10.1155/2021/6657639
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Substances in Safflower Flowers and Their Applicability in Medicine and Health-Promoting Foods

Abstract: Safflower flowers (Carthamus tinctorius) contain many natural substances with a wide range of economic uses. The most famous dye isolated from flower petals is hydroxysafflor A (HSYA), which has antibacterial, anti-inflammatory, and antioxidant properties. This review is aimed at updating the state of knowledge about their applicability in oncology, pulmonology, cardiology, gynecology, dermatology, gastrology, immunology, and suitability in the treatment of obesity and diabetes and its consequences with inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 97 publications
1
10
0
1
Order By: Relevance
“…H 2 S has also been effectively used in Carthamus tinctorius , an Asteraceae with essential medicinal properties and a source of food-grade color in the food industry [ 174 ]. The exogenous application of H 2 S (1 mM) on C. tinctorius plants subjected to drought demonstrated that the harmful effects caused by the water scarcity were countered, increasing the accumulation of secondary metabolites and antioxidant capacity [ 175 ].…”
Section: Ronss As Biostimulantsmentioning
confidence: 99%
“…H 2 S has also been effectively used in Carthamus tinctorius , an Asteraceae with essential medicinal properties and a source of food-grade color in the food industry [ 174 ]. The exogenous application of H 2 S (1 mM) on C. tinctorius plants subjected to drought demonstrated that the harmful effects caused by the water scarcity were countered, increasing the accumulation of secondary metabolites and antioxidant capacity [ 175 ].…”
Section: Ronss As Biostimulantsmentioning
confidence: 99%
“…Safflower is a traditional Chinese herbal medicine obtained from the dried corolla of Carthamus tinctorius L. In traditional Chinese medicine, the use of safflower promotes blood circulation and removes blood stasis (Adamska and Biernacka, 2021;Lu et al, 2021;Yao et al, 2016). Safflower extract was shown to promote the expression of vascular endothelial growth factor and keratinocyte growth factor in dermal papilla cells, thereby promoting the growth of living animal hair (Junlatat and Sripanidkulchai, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical groups isolated from Carthamus tinctorius are oils, proteins, minerals, phenolics, flavonoids, alkaloids, lignans, carboxylic acids, steroids, polysaccharides, quinochalcone C-glycosides and quinonecontaining chalcones. 8 Studies found that musk of Musk deer mainly contains macrocyclic ketones, pyridine, steroids, fatty acids, amino acids and proteins, whilst the main active ingredient is muscone. Modern pharmacological studies have proven that musk and muscone, the main active ingredient possess potent anti-inflammatory, neuroprotective, anticancer, and antioxidant effects and other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%